Bibliographie über die Wintersaateule, Agrotis segetum Denis und Schiffermüller (Lepidoptera, Noctuidae). - Rohlfien, Klaus; Friese, Gerrit; Hülbert, Dieter (Contributions to Entomology = Beiträge zur Entomologie, 1990)
The annotated bibliography about (Agrotis segetum) contains 476 works. An index with key-words leads to the quotations.